Effectiveness of Organic Transport Media on Induction Time, Sedation Time, Survival, and Molting of Cherax quadricarinatus - Tagema, Moh. Fauzan; Mulis; , Juliana (Sam Ratulangi University, 2026)
Cherax quadricarinatus is a high-value freshwater crustacean, yet live transportation remains a major challenge as it may reduce survival and induce physiological stress. This study aimed to evaluate the use of rice straw, coconut husk, and banana stem as organic packing media on induction time, sedation time, survival, and molting percentage of C. quadricarinatus juveniles. A completely randomized design was applied with three treatments (JP, SK, BP), each in triplicate, using a total of 90 juveniles (4–6 cm). Data were analyzed using ANOVA followed by the LSD test at a 95% confidence level. Results indicated that transport media influenced lobster physiological responses. Coconut husk resulted in relatively longer induction and sedation times, whereas banana stem yielded the highest survival rate and molting percentage. Although statistical differences were not significant, data trends confirmed the superiority of banana stem in maintaining moisture and physiological stability during transportation. This study recommends banana stem as an eco-friendly and effective organic medium for live transport of C. quadricarinatus juveniles. Keywords: Cherax quadricarinatus; dry transport; organic medium; survival Abstrak. Cherax quadricarinatus merupakan spesies krustasea air tawar bernilai ekonomi tinggi, namun transportasi hidup masih menjadi kendala utama karena dapat menurunkan kelangsungan hidup serta memicu stres fisiologis. Penelitian ini bertujuan mengevaluasi pemanfaatan jerami padi, sabut kelapa, serta batang pisang sebagai media organik transportasi terhadap waktu induksi, waktu sedatif, survival, serta persentase molting benih C. quadricarinatus. Rancangan acak lengkap digunakan dengan tiga perlakuan media (JP, SK, BP) masing-masing tiga ulangan, menggunakan total 90 ekor benih berukuran 4–6 cm. Data dianalisis menggunakan ANOVA serta uji BNT pada taraf kepercayaan 95%. Hasil penelitian menunjukkan bahwa media berpengaruh terhadap kondisi fisiologis lobster. Sabut kelapa menghasilkan waktu induksi dan sedatif relatif lebih lama, sedangkan batang pisang menunjukkan survival tertinggi serta persentase molting lebih besar dibandingkan dengan perlakuan lain. Meskipun perbedaan statistik tidak signifikan, tren data menegaskan bahwa batang pisang lebih efektif mempertahankan kelembapan serta stabilitas fisiologis selama transportasi. Penelitian ini merekomendasikan batang pisang sebagai media transportasi organik ramah lingkungan untuk mendukung distribusi benih C. quadricarinatus. Kata kunci: Cherax quadricarinatus; transportasi kering; media organik; survival